THE ROLE OF SOCIAL INSTITUTIONS IN THE DEVELOPMENT OF YOUNG PEOPLE - Muratova Dildora Abdumannapovna; Nazarova Nilufar Juraevna (Galaxy International Interdisciplinary Research Journal, 2022)
The family as a social institution plays an important role in the life of man and society. The article examines the readiness of the individual to perform family duties and analyzes the results of sociological research.